Efficient biosynthesis of β-caryophyllene by engineered Yarrowia lipolytica - Young-Kyoung Park; Lucie Studena; Piotr Hapeta; Ramdane Haddouche; David J. Bell; Pablo Torres-Montero; Jose Luis Martinez; Jean-Marc Nicaud; Adriana Botes; Rodrigo Ledesma-Amaro (Microbial Cell Factories)
Abstract Background β-Caryophyllene, a sesquiterpenoid, holds considerable potential in pharmaceutical, nutraceutical, cosmetic, and chemical industries. In order to overcome the limitation of β-caryophyllene production by the extraction from plants or chemical synthesis, we aimed the microbial production of β-caryophyllene in non-conventional yeast Yarrowia lipolytica in this study. Results Two genes, tHMG1 from S. cerevisiae to boost the mevalonate pool and QHS1 from Artemisia annua, were expressed under different promoters and copy numbers in Y. lipolytica. The co-expression of 8UAS pEYK1-QHS1 and pTEF-tHMG1 in the obese strain yielded 165.4 mg/L and 201.5 mg/L of β-caryophyllene in single and double copies, respectively. Employing the same combination of promoters and genes in wild-type-based strain with two copies resulted in a 1.36-fold increase in β-caryophyllene. The introduction of an additional three copies of 8UAS pEYK1-tHMG1 further augmented the β-caryophyllene, reaching 318.5 mg/L in flask fermentation. To maximize the production titer, we optimized the carbon source ratio between glucose and erythritol as well as fermentation condition that led to 798.1 mg/L of β-caryophyllene. Conclusions A biosynthetic pathway of β-caryophyllene was firstly investigated in Y. lipolytica in this study. Through the modulation of key enzyme expression, we successfully demonstrated an improvement in β-caryophyllene production. This strategy suggests its potential extension to studies involving the microbial production of various industrially relevant terpenes.